An Analysis of EFL Teacher's Lesson Plans for Learning English through Online Learning Platform in Junior High School - Ni Nyoman Diah Krisna Larasati; Dewa Komang Tantra; Luh Gd Rahayu Budiarta (Universitas Pendidikan Ganesha, 2021)
Learning planning requires the preparation and selection of learning objectives, learning media and resources, learning activities, and assessment instruments. The preparation of lesson plans for online learning through the use of google classroom is a new thing for teachers because teachers do not have experience in preparing online learning lesson plans. The purpose of this study was to analyze the preparation of lesson plans through google classroom based on a scientific approach to the K-13 curriculum. This study uses a qualitative research design, with the device used as an instrument covering aspects that include learning objectives, learning materials, learning activities, media, and learning resources, and learning benefits. The research subject in this study was an English teacher. The results of the study found that the RPP developed by teacher-developed well because the RPP also fulfilled 5 aspects of a complete RPP. Based on the results of the study, it can be said that the RPP developed can be applied in online learning, it has completed the 2013 Curriculum RPP material, and uses Google Classroom as an appropriate platform for online learning.